PENGARUH KEPEMIMPINAN, DISIPLIN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI - Wardaka, Adhitya Irvan; Pramusinto, Hengky (Business and Accounting Education Journal, 2020)
This study was aims to analyze the influence Leadership, Discipline, and Organization Cultur to Employee Performance both simultaneously or partially. The population of this study was 107 employees in the villages in Sukoharjo Sub-district Sukoharjo regency, Central Java. This research uses proportional random sampling as technique which is calculated using Slovin formula that produces 84 respondents. The data collection method was accomplished by doing also using questionnares, observation, interviews, and documentation. This research uses data analysis method with percentage descriptive analysis and regression analysis. The results showed that (1) there is a significant influence between leadership, discipline, and organization culture on employee performance in the villages in Sukoharjo Sub-district, (2) there is no significant influence between leadership on employee performance in the villages in Sukoharjo Sub-district, (3) there is a significant influence between discipline on employee performance in the villages in Sukoharjo Sub-district, (4) there is a significant influence between organization cultur on employee performance in the villages in Sukoharjo Sub-district.